Analisis Tingkat Kesehatan Bank Menggunakan Metode RGEC pada Bank BTN Syariah - Cut Punnariya Puteh; M. Ryzki Wiryawan (Ma'soem University, 2023)
The background of this research is that there is a gap between theory and reality. The purpose of this study is to analyze bank health using RGEC methods, namely Risk Profile, Good Corporate Governance (GCG), Earning, and Capital. This type of research is quantitative descriptive research using secondary data obtained from Bank BTN Syariah reports published on the Bank BTN Syariah website and the Financial Services Authority (OJK). The results of this research indicate that the health level of Bank BTN Syariah from 2018-2022, measured using the RGEC method based on the Risk Profile factor assessed with the NPF and FDR ratios, obtained a fairly healthy predicate with a value of 2.7. The GCG factor received a healthy predicate with a value of 2. The Earnings factor, evaluated with the ROA, ROE, BOPO, and NIM ratios, obtained a fairly healthy predicate with a value of 2.9. Lastly, the Capital factor, measured with the CAR ratio, received a very healthy predicate with a value of 1.